Critical writing patterns and learning strategies among vocational college students: Evidence from thesis writing - Zulmy Faqihuddin Putera; Suyono Suyono; Ahmad Rofiuddin; Titik Harsiati; Nurul Shofiah (ADGVI & Graduate School of Universitas Negeri Yogyakarta, 2025)
Developing critical writing skills remains a persistent challenge for vocational college students whose learning environments emphasize practical and technical competencies over academic discourse. Research specifically examining how vocational students demonstrate critical thinking in thesis writing is still limited. This study investigates (1) the patterns of critical writing that emerge in students’ thesis reports and (2) students’ perceptions of the strategies they use when engaging in critical writing. A qualitative design combining content analysis and thematic analysis was applied. Data were collected from 22 final thesis reports from 12 study programs and reflective statements and interviews with 10 Diploma-4 students. The analytical framework was adapted from Paul and Elder’s substantive writing skills. The findings show that vocational students demonstrate strengths in explanation and basic analysis; however, more advanced cognitive skills—such as synthesis, evaluation, and argument construction—remain weak. Students rarely develop counterarguments, critically examine opposing views, or integrate sources into coherent reasoning. Thematic analysis further reveals that students perceive critical writing as fulfilling structure and format rather than as a process of reasoning, evaluation, and synthesis. Difficulties are concentrated in topic delimitation, literature review, paraphrasing, and maintaining academic integrity, while supervisor feedback becomes the primary driver of writing progress. Overall, the study highlights a gap between students’ high motivation and their limited epistemic awareness of academic argumentation. These results emphasize the need for explicit instruction, structured scaffolding, and feedback focused on argument development rather than formatting. The study contributes to the literature by offering detailed insights into how critical writing develops within vocational higher education contexts and by proposing practical directions for instructional improvement.